Creation, development, exhibition and research of the “Pioneros del cine chaqueño” collection housed in the “Pablo Ducrós Hicken” Film Museum - Passarelli, Franco; Varela, Leandro (Cuadernos de Documentación Multimedia, 2024)
This article seeks to introduce the creation and development of the “Pioneros del Cine Chaqueño” Collection. A collection which is currently being stored at the Museo del Cine Pablo Ducrós Hicken in the Autonomous City of Buenos Aires, Argentina. This valuable collection is mainly made up of audiovisual elements in film format from the 1960’s and 1970’s, all of which were produced by filmmakers from the Chaco Province of Argentina. Approximately forty titles form this collection. These films cover a wide variety of genres including fiction, documentary, animation, experimental cinema and advertisement, among others. These productions, made entirely in the Chaco Province, have been historically excluded from the predominant narratives of Argentine national cinema, which traditionally center around Buenos Aires-based productions. The “Pioneros del Cine Chaqueño” Collection emerged from a research project of the same name, initiated in 2019 in the city of Resistencia, Chaco, under the tutelage of the Instituto de Investigaciones Geohistóricas (IIGHI, CONICET/UNNE). Through this project, more than eighty audiovisual works produced by entirely local production teams were identified and cataloged, although unfortunately more than half of these works have been lost or have not yet been found. This article seeks to offer a reflection on the collection and its importance, especially considering that its creators Franco Passarelli y Leandro Varela, are also the authors of this work. The research not only documents the genesis and development of the collection, but also highlights the need for research, preservation and dissemination of the audiovisual works in the collection. In this way, it aims to contribute to the historical and audiovisual memory of the Argentine Northeast region and also to help think about new film conservation projects in Argentina.
Keywords: Audiovisual preservation; archives; collection; cinema; Chaco